Validity of hydration non-invasive indices during the weightcutting and official weigh-in for Olympic combat sports - Fernandez-Elias, V. E.; Martinez-Abellan, A.; Lopez-Gullon, J. M.; Moran-Navarro, R.; Pallares, J. P.; de la Cruz-Sanchez, E.; Mora-Rodriguez, R. (PLOS ONE, 2014)
In Olympic combat sports, weight cutting is a common practice aimed to take advantage of competing in weight divisions below the athlete's normal weight. Fluid and food restriction in combination with dehydration (sauna and/or exercise induced profuse sweating) are common weight cut methods. However, the resultant hypohydration could adversely affect health and performance outcomes.